A Review of the Literature on Zakah between 2003 and 2019 - Rini, Rini (International Journal of Economics and Financial Issues, 2020)
This research aimed to critically review literature on the development of Zakah research from 2003 through 2019. This research employed a descriptive method and a qualitative approach. Classification is to be made into 8 categories of research, namely management, poverty, Zakah payment, organizational performance, collection and distribution, tax and Zakah, development and measurement of Zakah, and others. This research found that the topic garnering the most interest was poverty. This is because Zakah would reduce the poverty rate of a country. Keywords: Zakah Literature, Zakah Issues, Poverty JEL Classifications: Z12, N30, D64 DOI: https://doi.org/10.32479/ijefi.9035